Developmental differences in myocardial transmembrane Na+ transport: implications for excitability and Na+ handling - Oshiyama, Natália F.; Pereira, Ana H. M.; Cardoso, Alisson C.; Franchini, Kleber G.; Bassani, José W. M.; Bassani, Rosana A. (The Journal of physiology, 2022)
Little is currently known about possible developmental changes in myocardial Na+ handling, which may have impact on cell excitability and Ca2+ content. Resting intracellular Na+ concentration ([Na+]i), measured in freshly isolated rat ventricular myocytes with CoroNa green, was not significantly different in neonates (3–5 days old) and adults, but electrical stimulation caused marked [Na+]i rise only in neonates. Inhibition of L‐type Ca2+ current by CdCl2 abolished not only systolic Ca2+ transients, but also activity‐dependent intracellular Na+ accumulation in immature cells. This indicates that the main Na+ influx pathway during activity is the Na+/Ca2+ exchanger, rather than voltage‐dependent Na+ current (INa), which was not affected by CdCl2. In immature myocytes, INa density was two‐fold greater, inactivation was faster, and the current peak occurred at less negative transmembrane potential (Em) than in adults. Na+ channel steady‐state activation and inactivation curves in neonates showed a rightward shift, which should increase channel availability at diastolic Em, but also require greater depolarization for excitation, which was observed experimentally and reproduced in computer simulations. Ventricular mRNA levels of Nav1.1, Nav1.4 and Nav1.5 pore‐forming isoforms were greater in neonate ventricles, while a decrease was seen for the β1 subunit. Both molecular and biophysical changes in the channel profile may contribute to the differences in INa density and voltage‐dependence, and also to the less negative threshold Em, in neonates compared to adults. The apparently lower excitability in immature ventricle may confer protection against the development of spontaneous activity in this tissue. Key points Previous studies showed that myocardial preparations from immature rats are less sensitive to electrical field stimulation than adult preparations. Freshly isolated ventricular myocytes from neonatal rats showed lower excitability than adult cells, e.g. less negative threshold membrane potential and greater membrane depolarization required for action potential triggering. In addition to differences in mRNA levels for Na+ channel isoforms and greater Na+ current (INa) density, Na+ channel voltage‐dependence was shifted to the right in immature myocytes, which seems to be sufficient to decrease excitability, according to computer simulations. Only in neonatal myocytes did cyclic activity promote marked cytosolic Na+ accumulation, which was prevented by abolition of systolic Ca2+ transients by blockade of Ca2+ currents. Developmental changes in INa may account for the difference in action potential initiation parameters, but not for cytosolic Na+ accumulation, which seems to be due mainly to Na+/Ca2+ exchanger‐mediated Na+ influx. figure legend Little is currently known about possible developmental changes in myocardial Na+ transport, which may have impact on cell excitability and other physiological aspects. At the mRNA level, neonatal rat ventricle expresses a greater variety of Na+ channel isoforms than in adults. In immature ventricular cardiomyocytes, Na+ current (INa) density was greater, but voltage‐dependence is shifted to less negative potentials than in adults. This should increase channel availability at diastolic membrane potential, but also require greater depolarization for excitation, which was observed experimentally and reproduced in computer simulation. We also observed that electrical stimulation caused marked intracellular Na+ accumulation only in neonates, which was abolished when Ca2+ transients and the Na+/Ca2+ exchanger (NCX) were inhibited by Cd2+ + Ni2+. Thus, it seems that the main Na+ influx pathway during activity in neonates is the NCX, rather than voltage‐dependent INa, which was not affected by these blockers.